2023
DOI: 10.1115/1.4056768
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Rigid Interspinous Process Fixation Combined With Lumbar Interbody Fusion Using Hybrid Testing Protocol

Abstract: Rigid interspinous process fixation (RIPF) has been recently discussed as an alternative to pedicle screw fixation (PSF) for reducing trauma in lumbar interbody fusion (LIF) surgery. This study aimed to investigate biomechanics of the lumbar spine with RIPF, and also to compare biomechanical differences between two postoperative stages (before and after bony fusion). Based on an intact finite-element model of lumbosacral spine, the models of single-level LIF with RIPF or conventional PSF were developed and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The finite element study by Du et al also revealed that the ROM, IDP, and FJF of adjacent segments increased after lumbar interbody fusion because the pattern of motion and load distribution had been modified [ 9 ]. The reduced ROM of the fixed segment is compensated by other segments to restore the overall motor function of the spine, which can lead to an abnormal increase in IDP and FJF [ 10 ]. Thus, the published literature has mainly focused on reducing ROM, IDP, and FJF to alleviate ASD by improving surgical techniques, such as semirigid fixation and dynamic fixation [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The finite element study by Du et al also revealed that the ROM, IDP, and FJF of adjacent segments increased after lumbar interbody fusion because the pattern of motion and load distribution had been modified [ 9 ]. The reduced ROM of the fixed segment is compensated by other segments to restore the overall motor function of the spine, which can lead to an abnormal increase in IDP and FJF [ 10 ]. Thus, the published literature has mainly focused on reducing ROM, IDP, and FJF to alleviate ASD by improving surgical techniques, such as semirigid fixation and dynamic fixation [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a biomechanics perspective, the use of implants in fusion surgery, such as intervertebral cage and rigid fixator, can cause increased stiffness and thus result in load redistribution at neighboring levels. As a result, adjacent segments experience increased mobility and stress, which can contribute to the ASD development [ 2 - 4 ]. By considering this evidence associated with ASD, the dynamic implants made of more compliant materials were developed to establish stabilization and load-bearing capacity, while also allowing moderate motion in the instrumented segments [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%